(untitled) (Oratio Directa, 2023)
Public perceptions of former prisoners are sometimes excessive and may influence how former prisoners perceive themselves. Experiences of social discrimination also make it difficult for them to obtain decent employment. A constructive process of adaptation within society can gradually change the negative stigma directed at former prisoners. Their self-concept may develop negatively when social judgments are internalized. Self-concept is not merely a descriptive image of oneself, but also encompasses evaluations formed through interaction with other people and the surrounding social environment.